The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3153/jfscom.mug.200721
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of Birecik Dam Lake (Turkey) zooplankton

Abstract: nün zooplankton faunası araştırılmıştır. Çalışma sonucunda rotiferden 21, kladoserden 11 ve kopepoddan 7 olmak üzere toplam 39 tür belirlenmiştir. Rotifer türleri tüm su kesiminde bulunmakla beraber, daha çok yüzeye yakın yerlerde dağılım göstermiştir. Kladoser türlerinin daha çok orta su ve yüzeye yakın; kopepod türlerinin ise dibe yakın kısımlarda dağılım gösterdikleri belirlenmiştir. Ayrıca baraj gölündeki bazı su kalite parametreleri de ( Abstract:Vertical distribution of Birecik Dam Lake (Turkey) zooplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…(1) have been reported from less aquatic environment. It has also been reported that these species are found all or nearly all of the sampling periods (Bozkurt 1997;Bozkurt 2004aBozkurt , 2004bBozkurt and Dural 2005;Bozkurt 2006;Bozkurt and Sagat 2008;Bozkurt et al 2009;Bozkurt and Göksu 2010;Bozkurt and Güven 2010;Bozkurt and Tepe 2011;Ülgü and Bozkurt 2015;Bozkurt and Duysak 2016;Bozkurt 2016;Bozkurt and Aktaş 2016;Bozkurt 2017;Genç 2018a, 2018b;Bozca and Bozkurt 2018;.…”
Section: Discussionmentioning
confidence: 91%
“…(1) have been reported from less aquatic environment. It has also been reported that these species are found all or nearly all of the sampling periods (Bozkurt 1997;Bozkurt 2004aBozkurt , 2004bBozkurt and Dural 2005;Bozkurt 2006;Bozkurt and Sagat 2008;Bozkurt et al 2009;Bozkurt and Göksu 2010;Bozkurt and Güven 2010;Bozkurt and Tepe 2011;Ülgü and Bozkurt 2015;Bozkurt and Duysak 2016;Bozkurt 2016;Bozkurt and Aktaş 2016;Bozkurt 2017;Genç 2018a, 2018b;Bozca and Bozkurt 2018;.…”
Section: Discussionmentioning
confidence: 91%
“…A review of previous studies in Turkey revealed that 42 taxa were determined in Yenişehir Lake (Bozkurt, 2006); 38 taxa were identified in Yarseli Dam Lake (Bozkurt et al, 2004); 39 taxa were identified in Birecik Dam Lake (Bozkurt and Sagat, 2008); 17 were identified in Burdur Lake (Altındağ and Yiğit, 2002); 41 taxa were identified in Marmara Lake (Yıldız et al, 2007) by various researchers. In this respect, Kılavuzlu Dam Lake is more diverse than other reservoirs in terms of diversity of zooplankton species.…”
Section: Resultsmentioning
confidence: 99%
“…Results of some studies were as follow: totally 54 species were declared in Aslantaş Dam Lake, including 35 Rotifera, 14 Cladocera, and 5 Copepoda (Bozkurt et al, 2009;Bozkurt and Göksu, 2010); totally 39 taxa declared, containing 21 rotifer, 11 cladocer and 7 copepod in Birecik Dam Lake (Bozkurt and Sağat, 2008). Some others; 11 rotifer, 7 cladocer and 1 copepod, 19 species in total in Çamlıgöze Dam Lake, (Dirican and Musul, 2008); 2 cladocer, 5 copepod, 17 species in total in Devegeçidi Dam Lake, (Bekleyen, 2006); 8 cladocer, 2 copepod, 10 species in total in Çatalan Dam Lake, (Aladağ et al, 2006); 18 rotifer, 9 cladocer and 4 copepod, 31 species in total in Hirfanlı Dam Lake, (Yiğit and Altındağ, 2005); 11 rotifer in Kesikköprü Dam Lake (Yiğit, 2002); 21 rotifer, 7 cladocer and 4 copepod, 32 species in total in Kurtboğazı and Çamlıdere Dam Lakes (Demir, 2005); 8 cladocer and 4 copepod, 12 species in total in İkizcetepeler Dam Lake, (Alper et al, 2007); 34 rotifer at Devegeçidi Dam Lake (Bekleyen, 2001) and 28 rotifer, 16 cladocer and 3 copepod, 47 species in total were declared (Bekleyen, 2003).…”
Section: Discussionmentioning
confidence: 99%